Endogenous heparin-like syndrome in obstetrics: a series of observations in obstetrics - O. S. Beznoshchenko; K. A. Ostrik; O. A. Parfenova; B. V. Silaev (Вестник анестезиологии и реаниматологии)
Introduction. Endogenous heparin-like syndrome (HLS) in obstetrics is a rare complication characterized by the manifestation of the effect of heparin in the absence of its exogenous administration due to an increase in the concentration of glycosaminoglycans (GAG). Obstetric patients with HLS are at risk for the development of hemorrhagic complications in the perioperative period. The heterogeneity of the structure and anticoagulant activity of GAG complicates the laboratory diagnosis and therapy of HLS.The objective was to conduct a retrospective analysis of clinical observations of endogenous heparin-like syndrome in patients from an obstetric hospital and literature data on the diagnosis and therapy of hemorrhagic syndrome associated with HLS.Materials and methods. The retrospective analysis included 6 obstetric female patients treated on the basis of the Academician V. I. Kulakov National Medical Research Center of Obstetrics, Gynecology, and Perinatology, with laboratory signs of endogenous heparin-like syndrome (HLS).Results. Laboratory signs of HLS were detected in women after uterotomy, 5 had additional risk factors (thrombotic microangiopathy (TMA), placental abruption, preeclampsia, surgical correction of fetal spina bifida. The use of thromboelastometry, namely HEPTEM, made it possible to identify HLS. The bleeding was stopped after the administration of antifibrinolytic in observations № 2–5, however, the bleeding recurred in the woman in observation № 6 because non-specific therapy did not fully normalize thrombin generation, which was reduced under the influence of GAG.Conclusion. A clinically significant increase of endogenous GAG in the blood is a complex process. Female patients have high risk of bleeding associated with HLS need to laboratory monitoring of the hemostasis system in the perioperative period. Different laboratory methods, especially, tests with heparinase should be used to increase the probability of detecting HLS. TEM parameters allow for reasonable hemostatic therapy.